2021
DOI: 10.21601/jisem/11395
|View full text |Cite
|
Sign up to set email alerts
|

Review of Crowdfunding Regulations across Countries: A Systematic Review Study

Abstract: In recent years, the financial industry is seeing rapid implementation of an increasing number of new technologies. In crowdfunding campaigns, borrowers, potential investors, and platform providers may face some issues in terms of information disclosures, selecting an appropriate threshold, and platform insolvency. However, there is insufficient research to provide a cohesive view of the regulatory framework for crowdfunding platforms. This research offers comparative and comprehensive insights through a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…All these risks are further accelerated if the appropriate checks are not conducted on the fund seeker's creditworthiness, and they are not in a position to return the investors' monies. These investors may end up in liquidity risk (Alhammad et al, 2021). Like any investment system, the risk of money laundering is still present in crowdfunding financing because online platforms can be a suitable avenue for criminals to launder their proceeds of crime (Hidajat, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…All these risks are further accelerated if the appropriate checks are not conducted on the fund seeker's creditworthiness, and they are not in a position to return the investors' monies. These investors may end up in liquidity risk (Alhammad et al, 2021). Like any investment system, the risk of money laundering is still present in crowdfunding financing because online platforms can be a suitable avenue for criminals to launder their proceeds of crime (Hidajat, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Being aware of the severity of the above-mentioned risks, legislators across the globe have not remained insensitive and accordingly, regulations surrounding crowdfunding have been enacted in several countries such as USA, UK, Mauritius, Spain, Italy, Austria, Belgium, France, amongst others. A recent study conducted by Alhammad et al (2021) sought to assess the differences between crowdfunding regulations among 26 countries, including EU member countries, Asian countries and the USA. The researchers have found that there are specifically some common areas that are covered by the majority of crowdfunding legislation, mainly the authorisation process, fundraising limits, disclosures requirements, advertising policies, capital requirements rules, protection framework for clients' funds and platform-specific regulation concerning either exemptions or additional and miscellaneous requirements.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations